2012
DOI: 10.1186/1556-276x-7-480
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots: synthesis, bioapplications, and toxicity

Abstract: This review introduces quantum dots (QDs) and explores their properties, synthesis, applications, delivery systems in biology, and their toxicity. QDs are one of the first nanotechnologies to be integrated with the biological sciences and are widely anticipated to eventually find application in a number of commercial consumer and clinical products. They exhibit unique luminescence characteristics and electronic properties such as wide and continuous absorption spectra, narrow emission spectra, and high light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
259
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 504 publications
(262 citation statements)
references
References 157 publications
(131 reference statements)
0
259
0
3
Order By: Relevance
“…S4C). Hepato-renal toxicity is a well-known issue preventing the approval of QDs for biomedical applications, and the observed damage is likely attributed to the leakage of the QDs out of the LbL shell (34,35). To our knowledge, this is the first report of the head-to-head comparison of toxicities of NIR-II probes in an identical LbL platform.…”
Section: Resultsmentioning
confidence: 92%
“…S4C). Hepato-renal toxicity is a well-known issue preventing the approval of QDs for biomedical applications, and the observed damage is likely attributed to the leakage of the QDs out of the LbL shell (34,35). To our knowledge, this is the first report of the head-to-head comparison of toxicities of NIR-II probes in an identical LbL platform.…”
Section: Resultsmentioning
confidence: 92%
“…Some data suggest that QDs have very low toxicity, whereas other reports demonstrate that QDs may exert negative influence on cell viability, growth and development. [25] It was also found that biosynthesized CdS possess lower toxicity on plant, insect (our unpublished data) and non-human primate [26] cells. However, the toxicity of CdS semiconductor nanoparticles is associated with their physicochemical properties.…”
Section: Comparative Analysismentioning
confidence: 74%
“…Surface modification can increase the hydrophilicity of QDs and at the same time, reduce their toxicity. [25] It is the extracellular biosynthesis of nanoparticles by means of living organisms that can result in the production of water-soluble, stable and low-toxic luminescent nanoscale crystals because of their additional surface coating with biomolecules. Hence, the growing opinion that extracellular biosynthesis of nanoparticles could prove the most promising approach in nanobiotechnology.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Doxorubicin was encapsulated within this system with the floating and swelling method. Poly (NIPAAm-MAA-VP) magnetic nanocomposite loaded with Dox was characterized in terms of size and in-vitro release of doxorubicin (Valizadeh et al, 2012;Akbarzadeh et al, 2012a;2012b;2012c;2012d).…”
Section: Physicochemical Characteristics Of Fementioning
confidence: 99%